Maintenance of flower color dimorphism in Ophiorrhiza japonica (Rubiaceae): responses to fluctuating temperatures in a dolomite Karst region - Wang, Xiao-Yue; Tang, Han-Qing; Liu, Yun-Jing; Xiang, Meng-Da; Yao, Ren-Xiu; Li, Bai-Zhu; Li, Yu; Yi, Yin; Wen, Zhi-Rui; Tang, Ming; Tang, Xiao-Xin (Frontiers in Plant Science, 2024)
IntroductionFlower color polymorphism is often attributed to selection pressures from Q9 pollinators or other non-pollinator stress factors. Generally, flower color polymorphism demonstrates effective acclimatization linked to either pollinator-mediated selection or pleiotropic effects.MethodsTo test these hypotheses in Ophiorrhiza japonica, we compared pollinator visitation frequencies and plant traits between pink and white morphs in Shibing, a dolomite Karst region recognized as a World Natural Heritage Site. We also assessed the ratio of flower morphs and the reproductive success of the two morphs during spring and winter. Additionally, we examined the effects of temperature shifts on the two morphs under various temperature treatments.Results and discussionOur results revealed no significant difference in visitation frequencies between the morphs. However, the ratio of pink to white morph differed significantly between spring and winter. The temperature of pink morph was higher than that of white morph at temperatures ranging from 0-24°C, while white morph had higher temperatures than pink morph at -4°C. Based on the aforementioned results, pollinators are not the primary factor influencing the distribution of flower colors in spring and winter. Furthermore, the response of different flower colors to temperature suggests that temperature is more likely the factor driving changes in flower coloration. Our study provides further evidence supporting the pleiotropic effect hypothesis, which posits that flower color polymorphism can be maintained by fluctuating temperatures in the dolomite Karst region. This study offers a potential model for explaining flower color polymorphism in Karst regions.